Aromatase inhibitor strategies in metastatic breast cancer - Heather L McArthur; Patrick G Morris (Dove Medical Press, 2009)
Heather L McArthur, Patrick G MorrisBreast Cancer Medicine Service, Department of Medicine, Memorial Sloan-Kettering Cancer Center, New York, NY, USAAbstract: Despite ongoing therapeutic innovations, metastatic breast cancer (MBC) remains a treatable but incurable disease. In the developed world, a diagnosis of MBC without a preceding diagnosis of early stage disease is a rare event. However, approximately one-third of women with early stage breast cancer ultimately experience a distant recurrence. Because the majority of breast cancers express estrogen and/or progesterone receptors and are accordingly considered hormone-sensitive, therapeutic strategies that interfere with hormone-mediated tumorigenesis have been a cornerstone of the breast cancer management paradigm for decades. Historically, the selective estrogen receptor modulator tamoxifen has been the most extensively studied and widely used hormone maneuver in breast cancer. However, a recent therapeutic innovation, namely the successful development of third-generation aromatase inhibitors (AIs), has had a dramatic impact on the treatment paradigm for women with hormone-sensitive MBC. Because of the demonstrated efficacy in postmenopausal breast cancer patients, the generally favorable side-effect profile, and the convenience of oral administration, AIs are now in widespread clinical use. Currently, there are three clinically available third-generation AIs: two reversible, nonsteroidal AIs, letrozole and anastrozole; and one irreversible, steroidal AI, exemestane. All three agents are at least as efficacious as tamoxifen as monotherapy for postmenopausal women with hormone-sensitive MBC. Current clinical research aims to improve upon existing strategies by evaluating AIs in combination with systemic chemotherapy regimens and/or novel targeted agents. It is hoped that these therapeutic innovations will lead to ongoing improvements in quality of life parameters and ideally survival for women with hormone-sensitive MBC.Keywords: metastatic, breast cancer, aromatase inhibitors